2010
DOI: 10.3346/jkms.2010.25.11.1657
|View full text |Cite
|
Sign up to set email alerts
|

Determination of an Applicable FRAX Model in Korean Women

Abstract: We investigated which of the three FRAX fracture risk assessment tool models is most applicable to Korean women. For 306 postmenopausal women (mean age, 77 yr) with a hip fracture, fracture probabilities were calculated using FRAX models from Japan, Turkey and China. Data on bone mineral density (BMD) at the femoral neck were available for 103 patients. Significant differences existed among the models, independent of the inclusion of BMD in the calculation of fracture probabilities. The probabilities of both m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
2
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 12 publications
0
7
2
1
Order By: Relevance
“…The fracture probabilities of both major osteoporotic fractures and hip fractures significantly increased with age (7,16), but current study showed no significant age difference between the cases and the controls; this comes while in a similar study in Australia (2010), cases were on average five years older than the controls (17).…”
Section: Sexcontrasting
confidence: 74%
See 2 more Smart Citations
“…The fracture probabilities of both major osteoporotic fractures and hip fractures significantly increased with age (7,16), but current study showed no significant age difference between the cases and the controls; this comes while in a similar study in Australia (2010), cases were on average five years older than the controls (17).…”
Section: Sexcontrasting
confidence: 74%
“…Two hundred thirty six patients (77 men and 159 women) were enrolled in this study. From among them, 74 patients were Table 2 The predicted probabilities of hip and major fracture in both genders in the three studied models* tries are using a pre-existing model from a surrogate country (7).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Postmenopausal women from the general population were evaluated based on models from Japan, Turkey, and China. 9 The Japan model is suitable for Koreans, but these general population data produced higher scores for fracture probabilities than our data. Previous data on patients with proximal femoral fracture probabilities calculated using the Korean FRAX model produced higher scores than our data because our data involved a general population.…”
Section: Discussioncontrasting
confidence: 50%
“…Основная масса исследований по применению FRAX посвящена валидации этой методики в разных странах, сопоставлению данных о вероятности переломов внутри различных социальных, возрастных и других групп [36][37][38], анализу эффективности препаратов для лечения ОП и снижения риска переломов, а также сравнению чувствительности и специфичности метода FRAX и других методик для выявления лиц с ОП и высоким риском переломов [39,40].…”
unclassified